The Investment Rate of Return (IRR) to Tertiary Education in Turkey - Taskinsoy, John (Journal of Education and Vocational Research, 2012)
Most scholars, professionals, parents, governments, and societies strongly believe that education, especially tertiary education, provides important economic and social benefits to everyone involved. Furthermore, tertiary education is recently considered as an important investment. Students usually think of higher education in more personal terms, therefore they tend to pay less attention to the broader societal benefits, however tertiary education received immediately after secondary school can have considerable positive influence in countriesâ€™ economic development, further business growth, expansion to international markets and increase in living standards. Robert B. Zoellick, President of the World Bank Group 2010, said: â€œImproved learning leads to better jobs, greater productivity, and higher incomes in every society.â€1 This paper examines the IRR on tertiary education to first degrees, masterâ€™s degrees, and PhDs in Turkey using previously published data. The purposes of this research are to study and identify whether or not increase in tertiary education leads to increase in wages. Knowledge and advanced skills are critical determinants of a country’s economic growth and standard of living as learning outcomes are transformed into goods and services, greater institutional capacity, a more effective public sector, a stronger civil society, and a better investment climate2